Tempo and walking speed with music in the urban context - Franěk, Marek; van Noorden, Leon; Režný, Lukáš (Frontiers in Psychology, 2014)
The study explored the effect of music on the temporal aspects of walking behavior in a real outdoor urban setting. First, spontaneous synchronization between the beat of the music and step tempo was explored. The effect of motivational and non-motivational music (Karageorghis et al. 1999) on the walking speed was also studied. Finally, we investigated whether music can mask the effects of visual aspects of the walking route environment, which involve fluctuation of walking speed as a response to particular environmental settings. In two experiments, we asked participants to walk around an urban route through various environments in the downtown area of Hradec Králové. In Experiment 1, the participants listened to a musical track consisting of world pop music with a clear beat. In Experiment 2, participants were walking either with motivational music, which had a fast tempo and a strong rhythm, or with non-motivational music, which was slower, nice music, but with no strong implication to movement. Musical beat, as well as the sonic character of the music listened to while walking, influenced walking speed but did not lead to precise synchronization. It was found that many subjects did not spontaneously synchronize with the beat of the music at all, and some subjects synchronized only part of the time. The fast, energetic music increases the speed of the walking tempo, while slower, relaxing music makes the walking tempo slower. Further, it was found that listening to music with headphones while walking can mask the influence of the surrounding environment to some extent. Both motivational music and non-motivational music had a larger effect than the music from Experiment 1. Individual differences in responses to the music listened to while walking that were linked to extraversion and neuroticism were also observed. The findings described here could be useful in rhythmic stimulation for enhancing or recovering the features of movement performance.